Elephantine in context studies on the history, religion and literature of the Judeans in Persian period Egypt - Kratz, Reinhard Gregor 1957-; Schipper, Bernd U. 1968-; Mohr Siebeck GmbH & Co. KG (Tübingen Mohr Siebeck, 2022)
"The Persian period has long been considered a "dark era" in Israel's history. For this reason, research has mainly focused on how it is depicted in the Hebrew Bible. A spectacular discovery of archaeological relics and epigraphic sources was hence hardly noticed: the military colony located on the island of Elephantine in the Nile, on the border between Egypt and present-day Sudan. The basic approach of this volume, which documents a three-year Deutsche Forschungsgemeinschaft project, is to break with a research tradition focusing on the Judeans (Jews) mentioned in the Aramaic papyri from Elephantine and instead investigate the military colony in a broader historical context also documented by Demotic and Egyptian-hieratic evidence found at Elephantine. The studies presented focus on three main subject areas: society and administration, religion, and literature. They show that historically the island of Elephantine hosted a multicultural society with several interactions between the Egyptians and the other inhabitants, and that it was also an important administrative centre for the Persian authorities."
Description based on publisher supplied metadata and other sources
Keywords: Achaemenid dynasty -- 559-330 B.C -- History; Achaemenid dynasty - 559-330 B.C; Achaemenid dynasty - 559-330 B.C - History; To 1500; Jews -- Egypt -- Elephantine -- History -- To 1500; Electronic books; Jews; Religion; Jews - Egypt - Elephantine - History - To 70 A.D; Jews - Egypt - Civilization; Judaism - Egypt - History; History; Elephantine (Egypt) -- Religion; Éléphantine (Égypte) - Religion; Egypt - Elephantine; Elephantine (Egypt) - Religion; Aufsatzsammlung